AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN SELEDRI (Apium graveolens L) PADA MENCIT JANTAN - Fifteen Aprila Fajrin (Universitas Islam Indonesia, 2009)
ABSTRACTCelery (Apium graveolens L.) is one of plants that initially only used for cooking. Based onthe research by Wolski, et al., 2002, celery contains chemical compound such as tannins andpolyphenols. Tannins may be useful as an anti-diarrheal because of the adstringent effect. Thisstudy aims to determine the antidiarrheals activity of celery leaf in male mice strain Balb-C that wasinduced by castor oil. The ethanolic extract of celery leaves divided into three dose group (5,10 and20 mg/kgBW). This research was done by two methods, protection of castor oil induced diarrheaand intestinal transit. After five hours treatment, frequency of defecation, number of soft/liquidfeses and weight of stools were calculated. The gastrointestinal transit rate was expressed as thepercentage of longest distance traversed by the charcoal divided by the total length of the smallintestine.From the protection of castor oil induced diarrhea method, ethanol extract of celery 20mg/20gBW doses decrease frequency of defecation, quantity of the soft / liquid stool and weight ofstool after 5 hours treatment in male mice that had been induced by castor oil. The effectiveness ofethanol extract 20mg/20gBW dose equivalent to loperamid 0.06mg/20gBW (one way anova test atthe α = 95%). Besides, the ethanol extract of celery can prolong intestinal transit of mice, but lowerthan loperamid 0.06mg/20g (one-way anova test at the α = 95%).Keywords: antidiarrheal, castor oil, celery, intestinal transit, taninns